The Use of a Laser Diffractometer to Analyze the Particle Size Distribution of Selected Organic Soils - Grzegorz Straż; Małgorzata Szostek (Applied Sciences, 2024)
This study was conducted to verify the usefulness of the laser diffractometer method for determining the particle size distribution of selected organic soils from the Podkarpacie region in Poland. The soil selected for this research represented three main classification groups, namely, low-organic, medium-organic and high-organic soil, in accordance with the standard criterion. Particle size distribution was determined using two types of laser diffractometers: the Helos laser diffractometer manufactured by Sympatec GmbH (Clausthal-Zellerfeld, Germany) and the laser particle size analyzer Analysette 22 MicroTech plus manufactured by Fritsch GmbH (Idar-Oberstein, Germany). The standard mechanical and sedimentation methods, which are perfect for testing mineral soils, are not applicable to organic soils; therefore, a serious problem was found and examined. A reference method that could verify the test results obtained using the laser diffractometer methods was required. After analyzing the literature, the hydrometric (sedimentation) method was adopted as the reference method. Currently, there are no reliable and fully verified methods for testing soils with such a complex skeleton structure, and the resources, standards and guidelines concerning the issues discussed are extremely limited; therefore, new research methods are being sought to fill this gap, and this work is a step in this direction. The results of the conducted studies and analyses have shown that laser diffractometry methods can be useful for determining the particle size distribution of organic soils, but to a limited extent, depending mainly on the quantity of organic substances. The highest agreement was obtained by comparing the results of the sedimentation method with those obtained using the diffractometer analyzer Analysette 22 in the group of highly organic soils.